Rethinking writing support: Student satisfaction and writing development in a hybrid model in UAE higher education - Proff, Alexandria; Al-Shidrawi, Shadi Yacoub; Musalam, Rasha (Journal of International Students, 2026)
This study examines the effectiveness of a hybrid writing center at a university in the UAE. Using a quantitative, cross-sectional survey design (n=238), the research investigates the relationships between student satisfaction, service usage frequency, and perceived improvement in academic writing, comparing perceptions of online versus in-person support. Data were analyzed using ANOVA, paired t-tests, and ordinal logistic regression. Findings indicate that sustained engagement (five or more visits) is a significant predictor of higher satisfaction and perceived writing improvement, regardless of major or year. However, students perceived in-person services as significantly more effective than online alternatives (Cohen’s d = 1.22). These findings highlight the importance of hybrid and online learning environments in shaping international and multilingual students’ engagement with support services. This highlights the need to foster engagement while prioritizing the pedagogical design of online support as part of the movement toward virtual mobility and technology-enabled learning in higher education.